SOCIALIZATION OF MENTAL RECOVERY AND MOTIVATION FOR CHILDREN IN KUNING I VILLAGE: A HOLISTIC APPROACH TO PSYCHOLOGICAL WELL-BEING - Fitri Handayani (CV. Naskah Aceh, 2024)
Populations living in flood- prone areas will experience repeated floods . Repeated floods will have an impact on a person's health and well-being. Handling the impact of floods , especially psychological impacts such as anxiety, is by providing special interventions in the form of post-flood psychosocial assistance. The community service activities carried out aim to provide knowledge and skills to children regarding flood disaster preparedness and how to overcome anxiety due to flood disasters that occur. The method used is to provide health education and demonstrations then conduct an evaluation by comparing pretest and posttest values ​​using a questionnaire. The activity was carried out in March 2024 and was attended by 19 people. The results of community service showed that there was a significant difference in the average knowledge value before and after being given Disaster Preparedness Education and participants had the ability to overcome anxiety with breathing meditation techniques . Post- flood psychosocial assistance needs to be carried out as a promotive and preventive effort for communities in wetland environments that have the potential to experience repeated floods .